Efficacy and safety of oral mifepristone in induction of labour in prolonged pregnancy - Das, Rubby; Subedi, Nilam; Rajbhandari, Subrina; Gurung, Gahana (Journal of Kathmandu Medical College, 2022)
Background: Induction of labour implies, achieving vaginal delivery by stimulating uterine contractions before spontaneous onset of labour. Prolonged pregnancy exceeding duration of expected date of delivery is associated with increased risk to foetus and most common indication for induction of labour. Objectives: To study the safety and efficacy of oral mifepristone in induction of labour in prolonged pregnancy. Methods: This experimental study was carried out in Universal College of Medical Sciences Teaching Hospital, Bhairahawa between June 2016 to June 2017 after ethical clearance. Total 102 women were included in the study with 51 participants in the study group (mifepristone) and 51 in the control group (misoprostol). Data were expressed in frequency and mean ± SD and analysed using Independent “t” test and Chi-square test. A p-value of <0.05 was considered significant. Safety and efficacy of the drug was analysed with regards to maternal and perinatal outcome. Results: Single dose of mifepristone was sufficient enough for successful induction in 40 (78.43%) women in study group. Time interval from induction to delivery had maximum frequency of 6-12 hours in both groups (p-value 0.13). The active phase of labour lasted for 2-6 hours in 38 (74.5%) women of the study group. Around 27 (42.9%) women of study group required augmentation of labour and 49 (96.1%) women had vaginal delivery. There was no significant difference in perinatal outcome between both the groups. Conclusion: Mifepristone combined with or without augmentation is safe, efficient, economical, and convenient induction agent for initiation of labour in prolonged pregnancies.